2010
DOI: 10.2169/internalmedicine.49.3176
|View full text |Cite
|
Sign up to set email alerts
|

A Case of IgG4-related Lung Disease Associated with Multicentric Castleman's Disease and Lung Cancer

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Usually, causes of mortality of MCD include respiratory failure , renal failure, complication of infections, and progression to malignant lymphoma [11] . Previous reports have stated that IgG4-RD may develop as a complication of MCD in some cases, whereas both diseases may develop at the same time in some cases; therefore, discriminating one from the other has not been always easy [13] , [14] , [15] . The clinical picture of multicentric Castleman's disease (MCD) is characterized by various observations, such as fever due to excessive IL-6 production, high C-reactive protein (CRP) level, low albumin (Alb) level, and anemia; therefore, the effects of steroid monotherapy in patients with MCD are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, causes of mortality of MCD include respiratory failure , renal failure, complication of infections, and progression to malignant lymphoma [11] . Previous reports have stated that IgG4-RD may develop as a complication of MCD in some cases, whereas both diseases may develop at the same time in some cases; therefore, discriminating one from the other has not been always easy [13] , [14] , [15] . The clinical picture of multicentric Castleman's disease (MCD) is characterized by various observations, such as fever due to excessive IL-6 production, high C-reactive protein (CRP) level, low albumin (Alb) level, and anemia; therefore, the effects of steroid monotherapy in patients with MCD are limited.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies on the serum IL-6 levels in IgG4-RD have been published (23)(24)(25)(26). Yamamoto et al reported that 5 of 27 patients (19%) with systemic IgG4-RD presented with elevated serum levels of IL-6, however, the clinical features of such patients were unclear (23).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal coincidences of CD with lymphomas, B-cell non-Hodgkin, and Hodgkin lymphomas and with multiple myeloma were reported [18, 19]. A few reports described co-existence of CD (frequently unicentric and HV type) and solid neoplasms including ovarian, colorectal, bladder, renal, lung and tongue cancer, hepatocellular carcinoma, and retroperitoneal leiomyosarcoma, diagnosed in both early or advanced stages of disease [17, 20–25]. …”
Section: Discussionmentioning
confidence: 99%